Technical and Economic Assessment of Tomato Cultivation Through a Macro-Tunnel Production System with the Application of Gluconacetobacter diazotrophicus - Nelson Ceballos-Aguirre; Alejandro Hurtado-Salazar; Gloria M. Restrepo; Óscar J. Sánchez; María C. Hernández; Mauricio Montoya (Horticulturae)
Bacterial inoculants hold promise for enhancing the sustainability and profitability of tomato cultivation in macro-tunnel systems. This study aimed to evaluate the technical and economic viability of applying Gluconacetobacter diazotrophicus to tomato production. The separate addition of native G. diazotrophicus GIBI025 and GIBI029 isolates and a commercial inoculant containing Azotobacter chrococcum and Azospirillium sp. was evaluated at a rate of 1 × 108 CFU·mL−1 without nitrogen addition. Conventional fertilization treatment with no bacteria added and 100%-nitrogen fertilization relative to crop requirements (added as MAP and urea) was also assessed. The treatments were evaluated within the macro-tunnel production system. The experiment utilized a completely randomized block design with four replications per treatment, and each experimental unit consisted of 20 plants. The yield (kg·ha−1) was calculated and economic assessment was performed. The results show that native G. diazotrophicus isolates in tomato cultivation under the macro-tunnel production system improved its economic viability, achieving yields up to 95,501 kg·ha−1 without the addition of nitrogenous fertilizers. This research reveals benefit–cost ratios achieving 1.57 and net incomes reaching 16,707 US dollars per hectare. This work demonstrated that the native isolates assessed may be used in the pursuit of more integrated, sustainable, and competitive cultural practices.